TIG torch surfacing of metallic materials – a critical review - Mamat, M. Azwan; Maleque, Md. Abdul; Rahman, Md Mustafizur (Taylor & Francis, 2019)
This article aims to review and highlight the significant and development of tungsten inert gas (TIG) torch surfacing of metallic materials. The emphasis is on the surfacing method of metallic materials using melting processing route. The fusion surfacing methods such as powder injection, wire feed and preplace powder are elaborated. The comparison of TIG torch surfacing method compare to the electron beam welding, laser cladding and thermal spraying are tabulated to give a better understanding of each surfacing method. The application of TIG torch surfacing technique on various metallic materials is reviewed based on a number of works from previous researchers. The significant of processing variables of TIG torch surfacing technique are highlighted and it can be said that the heat input and welding speed are the most influential factors. This paper also showed the potential application of TIG torch surfacing for the hybridization of composite coated hard surface layer formation in metallic materials.